Assessing the Impact of Cultural Education Activities: the Problem of a Creation or when We Lose the Ability to Compare - Alperytė, Irena (Vilnius University Open Series, 2022)
In 2021, the association “Knowledge Economy Forum” published their research “The assessment of the impact of cultural education activities”. The mentioned paper included analysis of countries’ cultural education practices designed for children and youth (including Lithuania and its comparison to international practices). In general, the assessment of the impact of the existing cultural education “mapping” in Lithuania is welcomed, and this paper is based on empirical research. The most important drawback of the mentioned research is a lack of scientific criteria.
Keywords: culture; education; children/youth; creativity; impacts